2017
DOI: 10.3847/1538-4357/aa7d4d
|View full text |Cite
|
Sign up to set email alerts
|

Lyα Profile, Dust, and Prediction of Lyα Escape Fraction in Green Pea Galaxies

Abstract: We studied Lyman-α (Lyα) escape in a statistical sample of 43 Green Peas with HST/COS Lyα spectra. Green Peas are nearby star-forming galaxies with strong [OIII]λ5007 emission lines. Our sample is four times larger than the previous sample and covers a much more complete range of Green Pea properties. We found that about 2/3 of Green Peas are strong Lyα line emitters with rest-frame Lyα equivalent width > 20Å. The Lyα profiles of Green Peas are diverse. The Lyα escape fraction, defined as the ratio of observed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
244
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(283 citation statements)
references
References 96 publications
(138 reference statements)
36
244
3
Order By: Relevance
“…Comparing the extinction-corrected Lyα/Hβ flux ratio of 31.3 (Table 6) and the case B flux ratio of 31.9 obtained with the cloudy code (Ferland et al 1998(Ferland et al , 2013 for an electron temperature T e = 18300K and an electron number density N e = 1000 cm −3 , we find that the Lyα escape fraction is f esc (Lyα) = 98 per cent, the highest known so far for LyC leakers and other GP galaxies Izotov et al 2016a,b;Yang et al 2017). …”
Section: Lyα Emissionsupporting
confidence: 56%
“…Comparing the extinction-corrected Lyα/Hβ flux ratio of 31.3 (Table 6) and the case B flux ratio of 31.9 obtained with the cloudy code (Ferland et al 1998(Ferland et al , 2013 for an electron temperature T e = 18300K and an electron number density N e = 1000 cm −3 , we find that the Lyα escape fraction is f esc (Lyα) = 98 per cent, the highest known so far for LyC leakers and other GP galaxies Izotov et al 2016a,b;Yang et al 2017). …”
Section: Lyα Emissionsupporting
confidence: 56%
“…However, a Sersić fit is a simple parametrization that can be used even at high redshifts where spatial resolution is low, which means that using this simple geometric description increases the range of galaxies to which our results can be applied compared to more complex size measurements. Additionally the Sersić formulations was used by Yang et al (2017) to describe their galaxies which means that we can directly use their measurements when testing our predictions (see Section 4.3.1).…”
Section: Broadband Luminositiesmentioning
confidence: 99%
“…Two studies have previously derived relations of this kind. Yang et al (2017) construct a bivariate relation using the dust extinction and the velocity of the red Lyα peak and find an dispersion of approximately 0.3 dex. However, this prediction includes a parameter directly measured from the Lyα line which may limit its applicability in cases when Lyα is not detected, or the signal-tonoise is insufficient to properly determine the red peak velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, a homogeneous shell of neutral hydrogen (and dust) surrounding a Lyα and continuum emitting source (as first advocated by Ahn et al 2003) seems to be able to reproduce many observed line shapes from z ∼ 0 (Yang et al 2017) to higher redshifts (Verhamme et al 2008;Karman et al 2017). This has been shown using large libraries of pre-computed line shapes (Schaerer et al 2011;Gronke et al 2015) which can be compared to observations.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, the number of modeled spectra found in the literature are often merely individual spectra (e.g. Vanzella et al 2016;Dahle et al 2016) or compilations up to ∼ 10s (Hashimoto et al 2015;Karman et al 2017;Yang et al 2017). A (much) greater number of spectra will, thus, allow us to address the following questions:…”
Section: Introductionmentioning
confidence: 99%